Multiscale simulation of monoamine oxidase catalyzed decomposition of phenylethylamine analogs - Oanca, Gabriel; Stare, Jernej; Vianello, Robert; Mavri, Janez (European journal of pharmacology, 2017)
Phenylethylamine (PEA) is an endogenous amphetamine and its levels are increased by physical activity. As other biogenic monoamines, it is decomposed by monoamine oxidase (MAO) enzymes. The chemical mechanism of MAO, and flavoenzymes in general, is a subject of heated debate. We have previously shown that the rate-limiting step of MAO catalysis involves a hydride transfer from the substrate methylene group vicinal to the amino group to the N5 atom of the lumiflavin co-factor moiety. By using multiscale simulation on the Empirical Valence Bond (EVB) level, we studied the chemical reactivity of the monoamine oxidase B catalyzed decomposition of PEA and its two derivatives: p-chloro-β-methylphenylamine (p-CMP) and p-methoxy-β-methylphenethylamine (p-MMP). We calculated activation free energies of 17.1kcal/mol (PEA), 18.4kcal/mol (p-MMP) and 20.0kcal/mol (p-CMP), which are in excellent agreement with the experimental values of 16.7kcal/mol for PEA and 18.3kcal/mol for p-MMP, while the experimental value for p-CMP is not available. This gives strong support to the validity of our hydride transfer mechanism for both MAO A and B isoforms. The results are discussed in the context of the interplay between MAO point mutations and neuropsychiatric disorders.